Strategy Analysis Using the Business Model Canvas Method: Case Study: Hendy's Bakery in Tembung - Siregar, Nurul Haliza; Ramadhani, Sri; Harahap, Muhammad Ikhsan (Jurnal Manajemen Bisnis, 2024)
This research aims to analyze the Business Model Canvas of Hendys Bakery, which comprises nine elements: customer segments, value propositions, channels, customer relationships, revenue streams, key resources, key activities, key partnerships, and cost structure. The research adopts a qualitative descriptive research method, employing semi-structured interviews for data collection. The analysis reveals that Hendys Bakery's customer segments encompass individuals of all ages, including tourists visiting attractions in Deli Serdang Regency and Medan City. Value propositions consist of quality products with delicious and fresh taste (bread and cakes), attractive packaging, affordable prices, and a variety of more than eight product types. Customer relationships are fostered through effective communication, easy ordering processes, bulk purchase discounts, and secure packaging for online transactions. Channels for distribution include online promotions and sales via social media, direct sales, collaborations with large supermarkets, and participation in events or bazaars. The primary revenue streams for Hendys Bakery originate from direct sales and sales through gift shops, minimarkets, or supermarkets in Tembung. Key resources comprise production facilities, equipment, high-quality cake ingredients, and appealing packaging. Key activities involve diverse product manufacturing processes and direct sales. Key partnerships for Hendys Bakery include raw material suppliers (flour, butter, sugar producers), local government, financial institutions, supermarkets/minimarkets, and gift shops. To enhance its business model, Hendys Bakery needs to focus on improving customer relationships, channels, revenue streams, key resources, key activities, key partnerships, and cost structure. However, customer segment and value proposition elements require maintenance rather than improvement.